Acute septic arthritis of the knee: A rare case report of infection with Parvimonas micra after an intra-articular corticosteroid injection for osteoarthritis. (June 2018) - Sultan, Assem A.; Cantrell, William A.; Khlopas, Anton; Cole, Connor; Piuzzi, Nicolas S.; Sodhi, Nipun; Brooks, Peter; Mont, Michael A.
Abstract: Acute bacterial mono-articular septic arthritis affects most commonly the lower extremity joints in adult population and most commonly caused by Staphylococcus aureus . Various risk factors determine susceptibility to infection including host immunity, medical co-morbidity and joint structural abnormality and other organisms may be involved. Parvimonas micra ( P. micra ) is among the rare organisms that may be associated with atypical septic arthritis and primarily affects the native knee joint. Only 3 case reports in the literature have reported on pyogenic pyogenic joint infection caused by this organism. We hereby present our experience with a case of knee septic arthritis caused by P. micra in a patient with knee osteoarthritis following a recent intra-articular injection with corticosteroids. In susceptible patients, Intra-articular corticosteroid injection and crystal induced arthritis may propose a potential risk of contracting infection with P. micra . Highlights: A case report on native knee joint septic arthritis caused by rare anaerobic organism, Parvimonas Micra . Atypical clinical presentation of septic arthritis is highlighted through this case. Potential risk factors highlighted in this case is intra-articular injection with corticosteroids and the concurrent presence of calcium pyrophosphate crystals in the joint. Review of previous case reports and identified important clinical pearls are also discussed.